2017
DOI: 10.1021/acsami.7b16055
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C-Conjugated Nanoparticle Protects Cells from Oxidative Stress at Low Doses but Induces Oxidative Stress and Cell Death at High Doses

Abstract: Although the antioxidant property of vitamin C is well-known for protecting cells from oxidative stress, a recent study shows that it can also generate oxidative stress under a high intracellular concentration and induce cell death. However, poor chemical stability and low biological concentration (micromolar) of vitamin C restrict its function primarily as an antioxidant. Here, we report two different nanoparticle forms of vitamin C with its intact chemical stability, glucose-responsive release from nanoparti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
61
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 42 publications
5
61
0
Order By: Relevance
“…The hydrodynamic size of the resultant Si@AuNP and PAPM are 40-50 nm and 40-80 nm with ∼4-8 wt % and ∼10-13 wt % of vitamin C, respectively. The cellular oxidative stress was evaluated at two different vitamin C concentrations and found that at micromolar concentration it protects the cell, while at millimolar concentration it induces the cell death ( Figure 5b) by generating oxidative stress, particularly by producing H 2 O 2 , which disrupts the cellular redox balance [32].…”
Section: Dual Nanoparticles Nanoantioxidantmentioning
confidence: 99%
See 1 more Smart Citation
“…The hydrodynamic size of the resultant Si@AuNP and PAPM are 40-50 nm and 40-80 nm with ∼4-8 wt % and ∼10-13 wt % of vitamin C, respectively. The cellular oxidative stress was evaluated at two different vitamin C concentrations and found that at micromolar concentration it protects the cell, while at millimolar concentration it induces the cell death ( Figure 5b) by generating oxidative stress, particularly by producing H 2 O 2 , which disrupts the cellular redox balance [32].…”
Section: Dual Nanoparticles Nanoantioxidantmentioning
confidence: 99%
“…(a) Schematic presentation on the synthesis of vitamin C conjugated nanoparticles (Si@AuNP or PAPM) and (b) cellular oxidative stress at micro and millimolar concentration of vitamin C. Adapted with permission from Ref [32]…”
mentioning
confidence: 99%
“…Vitamin C exerted nonenzymatic antioxidant function by destroying free radicals and trapping them in the aqueous phase to protect the biological membrane [21,22]. However, there is a report that high doses of vitamin C have been suggested to cause oxidative stress and cell death [23]. Despite its widespread use as a potent antioxidant in the field of medicine, its use is limited.…”
Section: Introductionmentioning
confidence: 99%
“…The delivery via conjugates is not limited to drugs, but can be extended to substances such as those useful in medical cosmetology, usually vitamins, such as vitamin E [ 25 , 26 , 27 ], vitamin B12 [ 28 ], folic acid [ 29 ], vitamin C [ 30 ] and vitamin A [ 31 , 32 ]. In most of these studies, they have played the role of a co-delivery substances to assist the carrier in the efficient delivery of anti-cancer drugs indicating a desired cytotoxicity against cancer cells and higher effect of apoptosis than the free drug, diverse drug resistance and reduced side inflammation, or cell protection from oxidative stress at allowed doses.…”
Section: Introductionmentioning
confidence: 99%